2020
DOI: 10.1016/j.cub.2019.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Models of Larval Zebrafish Behavior Reveal Structure on Many Scales

Abstract: Highlights d Naturalistic larval zebrafish behavior is observed with a moving camera system d Probabilistic models are used to predict and simulate behavioral sequences d Models combine environmental dynamics, behavioral history, and hunger state d Simulations capture behavioral dynamics spanning multiple timescales

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 80 publications
4
103
0
Order By: Relevance
“…An advantage of using one-week-old zebrafish is that the repertoire of their swims has been described and can be clustered into movement types through automatic, unsupervised methods [Marques et al, 2018, Johnson et al, 2020, Mearns et al, 2020], enabling exact phenotyping of behavioral events. Using this technology, we found that larvae avoid each other by executing four types of large displacement bouts: burst swims [Severi et al, 2014], long capture swims [Marques et al, 2018], O-bends [Burgess and Granato, 2007b], and C-starts (LLCs and SLCs) [Burgess and Granato, 2007a].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An advantage of using one-week-old zebrafish is that the repertoire of their swims has been described and can be clustered into movement types through automatic, unsupervised methods [Marques et al, 2018, Johnson et al, 2020, Mearns et al, 2020], enabling exact phenotyping of behavioral events. Using this technology, we found that larvae avoid each other by executing four types of large displacement bouts: burst swims [Severi et al, 2014], long capture swims [Marques et al, 2018], O-bends [Burgess and Granato, 2007b], and C-starts (LLCs and SLCs) [Burgess and Granato, 2007a].…”
Section: Discussionmentioning
confidence: 99%
“…Second, larvae are small and transparent enough to enable whole brain imaging with single neuron resolution in behaving animals [Feierstein et al, 2015], including freely moving fish [Kim et al, 2017, Marques et al, 2020, Cong et al, 2017], an ideal situation where animals can interact with each other. Finally, larval zebrafish organize their behaviors, including social interactions, in sequences of discrete bouts [Budick and O’Malley, 2000, Fero et al, 2011], which can be detected automatically and classified into types [Mirat et al, 2013, Marques et al, 2018, Mearns et al, 2020, Johnson et al, 2020], enabling precise behavioral phenotyping.…”
Section: Introductionmentioning
confidence: 99%
“…Second, affecting complex behavioral states such as aggression, addiction, social behavior, or learning may improve resolution. We used a trivial readout for potentially high-dimensional movement behaviors, but tracking, 48 optic flow, 40 probabilistic models, 17 and deep learning 15 have been successful in analyzing similar data. Future studies will likely leverage advances in all these areas to improve the resolution of zebrafish behavioral profiling assays.…”
Section: Discussionmentioning
confidence: 99%
“…Motifs correspond to recurring sequences of elementary locomotor episodes of arbitrary length. A well-established motif for larval zebrafish corresponds to the sequence of locomotor episodes consisting of a J-turn followed by pursuit and capture swims deployed for hunting prey [17,25,26]. BASS considers sequences rather than individual locomotor episodes and has the following advantages: 1) BASS does not need to know the sensory information perceived by the animal, 2) BASS captures extended responses that last much longer than a typical locomotor episode, 3) BASS identifies conserved sequences despite them rarely occurring in the behavioral recording.…”
Section: Introductionmentioning
confidence: 99%
“…In order to survive, five days old zebrafish larvae actively explore their environment avoiding toxic cues and searching for food using stereotypical locomotor episodes consisting of bouts of activity lasting few hundreds of milliseconds separated by distinct pauses [16,17,25,33].…”
Section: Introductionmentioning
confidence: 99%